Analisis Perancangan Sistem Informasi Tabungan Sekolah Dasar XYZ Menggunakan Metode Waterfall dan PIECES - Eko Setiawan; Ahmad Subhan Yazid (STMIK Banjarbaru, 2025)
School savings at SD XYZ have been managed manually, so there are often obstacles such as inefficient data management and lack of transparency for teachers and parents. This research aims to design a website-based information system to facilitate the management of student savings, payment of Student Worksheets (LKS), books, courses, and other needs. The Waterfall model is implemented in system development through the stages of analysis, design, implementation, and maintenance. Needs analysis is carried out with the PIECES (Performance, Information, Economy, Control, Efficiency, Service) approach. System testing is done using the black box testing method to ensure each feature works according to its function. The test results show that all features, such as login, savings mutation, payment, and savings report, function properly according to the test scenario. The system is considered feasible to use because it is able to provide accurate information, improve the efficiency of the administrative process, and provide transparent access for teachers and parents to monitor data online.Keywords: School savings; Information system; Waterfall method; PIECES; school administration AbstrakTabungan sekolah di SD XYZ selama ini dikelola secara manual, sehingga sering terjadi kendala seperti pengelolaan data yang kurang efisien dan minimnya transparansi bagi guru serta orang tua. Penelitian ini bertujuan untuk merancang sistem informasi berbasis website guna memudahkan pengelolaan tabungan siswa, pembayaran Lembar Kerja Siswa (LKS), buku, kursus, serta kebutuhan lainnya. Model Waterfall diterapkan dalam pengembangan sistem melalui tahapan analisis, desain, implementasi, dan pemeliharaan. Analisis kebutuhan dilakukan dengan pendekatan PIECES (Performance, Information, Economy, Control, Efficiency, Service). Pengujian sistem dilakukan menggunakan metode Black box testing untuk memastikan setiap fitur bekerja sesuai fungsinya. Hasil pengujian menunjukkan seluruh fitur, seperti login, mutasi tabungan, pembayaran, serta laporan tabungan, berfungsi dengan baik sesuai skenario uji. Sistem dinilai layak digunakan karena mampu menyediakan informasi yang akurat, meningkatkan efisiensi proses administrasi, serta memberikan akses transparan bagi guru dan orang tua untuk memantau data secara online.Kata kunci: Tabungan sekolah; Sistem informasi; Metode Waterfall; PIECES; Administrasi sekolah